Sosialisasi Tata Cara Promosi Kepada Pelaku UMKM Di UP2K Lanjung Uma, Kelurahan Alalak Utara, Kecamatan Banjarmasin Utara, Kota Banjarmasin - Nurul Hayati; Norbaiti Norbaiti (Training & Research Institute - Jeramba Ilmu Sukses, 2020)
This community service took the topic of the Socialization of Promotion Procedures to MSME Players at UP2K Lanjung Uma, Alalak Utara Village, North Banjarmasin District, Banjarmasin City. The implementation of this community event is by providing socialization on the procedures for business promotion. The goal is that MSMEs at UP2K Lanjung Uma, Alalak Utara Village, North Banjarmasin District, Banjarmasin City, can increase the percentage of sales. This community service program funded by STIE Indonesia Banjarmasin is Rp. 5,000,000. The first week of implementation stages, the location survey at UP2K Lanjung Uma. The second week, held an interview about business motivation and entrepreneurship. The fourth week, provides counseling about, determining market segments and promotion procedures. The fifth week of evaluation of outreach and training. The results of the activity team's observations, first obtained that the training and guidance participants understand marketing management especially the process / quality of production, promotion, packaging and health. Second, the participants can determine target consumers. Third, the quality of their production participants is maintained and the waste does not damage the environment. Fourth, media promotion with online social media. Fifth, providing facilities and infrastructure, such as glass cabinets or storefronts so that it is easier to display products.